2021
DOI: 10.1021/acs.jafc.1c00797
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Detection of Sulfur Dioxide Derivatives by a Distinctive “Dual-Positive-Ion” Platform that Features a Doubly Activated but Irreversible Michael Addition Site

Abstract: Sulfur dioxide (SO 2 ) is a gaseous signaling molecule and widely used as a preservative for foods, but its excessive intake is closely related to a series of diseases. Therefore, the development of a potent fluorescence probe for the detection of SO 2 in foods and biological systems is of great significance. Herein, we report for the first time a "dual-positive-ion" platform-based fluorescence probe CMQ, designed by a doubly activated but irreversible strategy, which results in its ultrafast response to SO 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The response points on the array were designed based on six specic color reactions that could occur with sulte in conventional spectrophotometry. [30][31][32][33][34][35] These specic reactions were shown in Fig. S1.…”
Section: Array Responsementioning
confidence: 99%
See 1 more Smart Citation
“…The response points on the array were designed based on six specic color reactions that could occur with sulte in conventional spectrophotometry. [30][31][32][33][34][35] These specic reactions were shown in Fig. S1.…”
Section: Array Responsementioning
confidence: 99%
“…In particular, in addition to TCM, it has been reported that the sulfur-fumigation process has been illegally used in many foods and food ingredients (e.g., star anise, pepper, wolerry, ginger, fungus and tremella). 10,14 Currently, the pharmacopoeias and food laws of many countries and regions have stipulated the limits of sulfur dioxide residues and recommended a variety of detection methods for sulfur dioxide residue, such as spectrophotometry, 15 acid-base titration, 16 uorescence method, 17,18 gas chromatography-mass spectrometry, 19 high-performance liquid chromatography, 20 electrochemical analysis, 21 enzyme-linked immunosorbent assays 22 and Fourier-transform infrared spectroscopy. 23 Although the above-mentioned means exhibit high sensitivity and selectivity, their popularization and application are generally limited by high costs, unfriendly portability, complex sample pretreatment, and specialized technical training in some developing countries and regions.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with classical detection methods including chromatography, electrochemistry, , and capillary electrophoresis, , the fluorescence imaging method has received unprecedented attention in recent years due to its high selectivity, good sensitivity, facile and noninvasiveness operation, high temporal and spatial resolution, and real-time sensing. Thus far, a surging number of fluorescent probes have been developed as powerful tools for the determination of HSO 3 – /SO 3 2– based on nucleophilic addition, deprotection reaction, , hydrogen bonding recognition, , and other chemical reaction mechanisms. , Regretfully, most of them mainly depended on single fluorescence signal changes, which are easily interfered by probe concentration, instrumental artifacts, and variations in cellular medium, thus hampering the reliability of the fluorescent assay. , To address this issue, ratiometric fluorescence probes with two different emission intensities, which could afford a built-in correction property and eliminate environmental effects, are popular nowadays.…”
Section: Introductionmentioning
confidence: 99%